2015
DOI: 10.1002/anie.201410295
|View full text |Cite
|
Sign up to set email alerts
|

The Structure and Optical Properties of the [Au18(SR)14] Nanocluster

Abstract: Decreasing the core size is one of the best ways to study the evolution from Au(I) complexes into Au nanoclusters. Toward this goal, we successfully synthesized the [Au18(SC6H11)14] nanocluster using the [Au18(SG)14] (SG=L-glutathione) nanocluster as the starting material to react with cyclohexylthiol, and determined the X-ray structure of the cyclohexylthiol-protected [Au18(C6H11S)14] nanocluster. The [Au18(SR)14] cluster has a Au9 bi-octahedral kernel (or inner core). This Au9 inner core is built by two octa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
197
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 221 publications
(213 citation statements)
references
References 43 publications
13
197
1
Order By: Relevance
“…[ 57 ] The Au 20 pyramid was observed to be present in solution with triphenylphosphine (PPh 3 ) ligands using a synthetic procedure for gold nanoparticles. [ 58 ] The pyramidal structure and the electronic properties of the T d Au 20 (PPh 3 ) 4 cluster were shown computationally to be similar to those of the bare Au 20 . [ 58 ] However, in order to obtain large quantities of pure pyramidal Au 20 samples and investigate its interesting catalytic and optical properties, a high yield synthetic method is needed.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…[ 57 ] The Au 20 pyramid was observed to be present in solution with triphenylphosphine (PPh 3 ) ligands using a synthetic procedure for gold nanoparticles. [ 58 ] The pyramidal structure and the electronic properties of the T d Au 20 (PPh 3 ) 4 cluster were shown computationally to be similar to those of the bare Au 20 . [ 58 ] However, in order to obtain large quantities of pure pyramidal Au 20 samples and investigate its interesting catalytic and optical properties, a high yield synthetic method is needed.…”
Section: Introductionmentioning
confidence: 83%
“…For gold cores with different nuclearity, or even the same nuclearity with different structures, the spectra will show totally different absorption peaks. For example, although both [Au 6 (dppp) 4 ] 2+ and [Au 7 (dppp) 4 ] 3+ have four 1,3-bis(diphenyl-phosphino)propane (dppp) ligands, their UV-Vis-NIR spectra show different peaks at 587 and 556 nm, respectively, [ 37 ] due to the different nuclearity. It has also been reported that the [Au 6 (dppp) 4 6 ] 3+ clusters all have structures consisting of a gold core with addition atoms outside the core (core+exo) and they all have different absorption features, when compared with the core-only Au nanoclusters of the same nuclearity.…”
Section: Uv-vis-nir Spectroscopy Of Phosphine-protected Auncsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the elucidation of the Au 102 (SR) 44 NC in 2007 [19], the catalog of possible Au core geometries and stabilizing surface structures from solved crystal structures and DFT predictions has grown significantly [20]. To date, icosahedral, face-centered-cubic (FCC)-ordered and smaller Au core ( < 13 Au atoms) structures have been reported crystallographically for various Au n (SR) m sizes [19,[21][22][23][24][25][26][27][28][29][30]. A couple of selenolate-protected Au NCs have also been recently elucidated with icosahedral or small Au 8 core structures [31,32].…”
Section: Introduction To Gold Nanoclustersmentioning
confidence: 99%
“…A couple of selenolate-protected Au NCs have also been recently elucidated with icosahedral or small Au 8 core structures [31,32]. In the last few years, a number of surface structures in addition to the monomeric and dimeric staple-like motifs were identified such as a trimeric staple-like motif [28], tetrameric staple-like motif [29,30], μ 3 sulfide coordination [25], bridging thiolate motif [24], and ring-like motifs (long Au-SR oligomers) [27,33]. Figure 1 presents the diversity of thiolate-protected Au NC structures.…”
Section: Introduction To Gold Nanoclustersmentioning
confidence: 99%